Pelatihan Membangun Jaringan RT/RW Net pada Karang Taruna Desa Kemelak Baturaja Timur - sri hartati; Rusidi Rusidi (Jurnal Pengabdian Masyarakat (abdira), 2022)
Breaking the chain of spread of covid-19 is by doing social distancing. Social distancing causes many activities to turn to online. Online activities have increased people's internet needs. The Internet is currently a staple for students, students, traders and even office employees who carry out Work From Home (WFH). Therefore, a good internet network is needed so that online activities run smoothly. The youths of Kemelak Village of East Baturaja District who are members of the Karang Taruna organization took the initiative to install their internet network. But the limitations of knowledge in building this internet network then held training to build an internet network called RT / RW Net Network Kemelak Village East Baturaja District. With this training is expected to provide enough knowledge to the youth of Karang taruna kemelak Village East Baturaja District in building an internet network. So, Kemelak Village of East Baturaja District will be able to build its internet network implemented by Karang taruna.